Anterograde techniques for percutaneous revascularization of chronic total coronary occlusions. (June 2010) - Galassi, Alfredo R; Tomasello, Salvatore D; Costanzo, Luca; Tamburino, Corrado
Percutaneous coronary intervention for chronic total occlusions remains one of the major challenges in interventional cardiology. To improve results in term of angiographic success from the historically quoted rates of 50–60% to the levels now routinely quoted by expert operators, skill, experience and also a complete knowledge of the wide array of techniques and tools armamentarium available are needed. The anterograde approach is the most frequent technique chosen in percutaneous coronary intervention chronic total occlusions, but it requires a great understanding of the different guidewires and specific materials available that is seperate from the understanding of the type of lesion being faced. In this article, we sought to list and describe the anterograde techniques available to perform chronic total occlusion percutaneous coronary intervention and also to deal with the most common procedural complications. A complete understanding of all techniques is needed for the operators to choose the most appropriate technique in relation to the lesion characteristics, and enables the operator to switch during the procedure from one technique to another in case of technical failure.